Light interaction between gold nanoshells plasmon resonance and planar optical waveguides - Lal, Surbhi; Westcott, Sarah; Klupp Taylor, Robin; Jackson, Joseph; Nordlander, Peter; Halas, Naomi (Journal of Physical Chemistry B, 2002)
We have studied the experimental and theoretical aspects of the interaction of gold nanoshells on a waveguiding structure. Gold nanoshells are core−shell particles consisting of a silica core surrounded by a thin gold shell. The waveguiding structure consists of a 2 μm thick layer of gold with a dielectric layer of varying thickness deposited on it. Light scattering experiments performed on gold nanoshells randomly deposited on the dielectric layer show a change in the scattering spectrum of the nanoshells because of coupling of light with the waveguide modes. Comparison of experimental data with theoretical calculations based on the classic theory of point dipoles placed over a conducting surface shows a significant shift in the dipole resonance position. A simple image charge calculation taking into consideration finite size effects explains the red shift observed in the experimental data for the smallest dielectric layer thickness. Observed deviations from the theoretical models are attributable to nanoshell aggregate
Keywords: plasmon; nanoparticle; optics; shell; core; particle